Global functioning among middle-aged patients with chronic schizophrenia: the role of medication, working memory and verbal comprehension - Ruiz-Iriondo, Maria; Salaberria, Karmele; Echeburua, Enrique; Iruin, Alvaro; Gabaldón Poc, Olga; Fernández Marañón, Idoia (Anales de Psicología / Annals of Psychology, 2019)
The chronic phase of schizophrenia is characterized by illness progression and patients encountering difficulties to return to premorbid level of functioning. The objective of this study was to describe the characteristics of a sample of patients with chronic schizophrenia, as well to assess differences between patients under and over 45 years of age. In a clinical sample of 77 chronic schizophrenia patients, we assessed basic symptoms, cognitive performance, social functioning and quality of life. All participants obtained very high scores in residual symptoms, and no differences in sociodemographic or clinical characteristics between the age groups were found. Younger patients had better cognitive performance and older patients obtained better scores for social functioning and quality of life. Number of psychotropic drugs, verbal learning delayed of SCIP, errors in WCST, Similarities and Digit Symbol Coding of WAIS were the most important variables to predict global functioning of patients over 45 years old. Increasing our understanding of differences in characteristics of the chronic phase of the illness and the profile of functioning at different ages, may help us design intervention strategies to improve adaptation in young and middle-aged patients with chronic schizophrenia.